Hi there!
»»————- ★ ————-««
I believe your answer is:
[tex]\boxed{x-1+x-2+x}[/tex]
»»————- ★ ————-««
Here’s why:
⸻⸻⸻⸻
[tex]\boxed{\text{Simplifying the Expression...}}\\\\3x+2+(-5)\\----------------\\\rightarrow 3x+2-5\\\\\rightarrow\boxed{3x-3}\\\\\text{This is not an answer choice, so we would find an expression equivalent to the one above.}[/tex]⸻⸻⸻⸻
[tex]\boxed{2 +3x+5}\\\\\rightarrow 3x + 5 + 2\\\\\rightarrow \boxed{3x + 7}\\\\\text{This is \textbf{NOT} equivalent.}[/tex]
⸻⸻⸻⸻
[tex]\boxed{x-1+x-2+x}}\\\\\rightarrow x+x+x -1-2\\\\\rightarrow \boxed{3x-3}\\\\\text{This is \textbf{equivalent}.}\\\\\text{This answer choice and the expression given has the same result when simplified.}[/tex]
⸻⸻⸻⸻
[tex]\boxed{-3-3x-1+x}}\\\\\rightarrow-3-1-3x+x\\\\\rightarrow -4-2x\\\\\rightarrow \boxed{-2x-4}\\\\\text{This is \textbf{NOT} equivalent.}[/tex]
⸻⸻⸻⸻
[tex]\boxed{3-3x}\\\\\rightarrow{-3x+3}\\\\\text{This is \textbf{NOT} equivalent.}[/tex]
⸻⸻⸻⸻
[tex]\text{Option B, } x-1 +x-2 + x, \text{ should be the correct answer.}[/tex]
»»————- ★ ————-««
Hope this helps you. I apologize if it’s incorrect.